Synthesis of Two Novel Mixed Bifunctional Chelating Agents: DO2AP(tBu)4 and DO3AP(tBu)4 - Travagin, Fabio; Biondi, Luca; Lattuada, Luciano; Giovenzana, Giovanni B. (Synlett, 2020)
A convenient synthesis of two novel macrocyclic bifunctional chelating agents (BFCAs), formally derived from the well-known ligands DO3A and DOTA by selective replacement of one carboxymethyl side arm with a phosphonomethyl residue, is reported.
Keywords: bifunctional chelating agents; DO3A; DOTA; phosphonic group; protecting group